INVASIVE CANDIDIASIS IN PRETERM NEWBORN: A CASE REPORT - Milicevic, Aleksandar (Acta medica Medianae, 2022)
Candida is the main etiologic factor in the development of invasive fungal infections in children in the hospital environment. We reported our autopsy findings from clinically undiagnosed neonatal invasive candidiasis. Male preterm newborn 27 gestational weeks old died after 24 days after delivery with clinical diagnosis of intracranial and intrapulmonary hemorrhage, threated with surfactant, antibiotics and invasive mechanical ventilation. Histologically, multiple colonies of fungi were found in lung blood vessels, kidney, suprarenal gland, brain, endocardial and myocardial tissue. In the liver, centrilobular necrosis was found.